Penilaian Publik terhadap Aplikasi Peduli Lindungi (Analisis Komparasi terhadap Aspek Demografi) - Rifki Nur Priyansyah; Ikhsan Fuady (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2023)
The Indonesian government has utilized an application, named Peduli Lindungi, to assist in controlling the spread of Covid-19. This study was aimed to uncover the public’s views on the Peduli Lindungi application. An online survey was conducted by distributing the questionnaire through social media applications to gather 266 participants around Indonesian inhabitants using a convenience sampling method. The data were analyzed by applying an independent sample t-test and ANOVA to detect the differences of participants’ usefulness and easiness perception, attitude, privacy anxiety, and trust between gender, age, educational level, and occupation groups. The analysis showed that oldsters, graduate degree completion, and public workers had a higher level of perceived usefulness, attitude, and trust. The study also found the role of educational level and occupation in affecting the public’s perception. However, more studies are encouraged by broadly observing other types of views to design the most effective strategy in promoting the application.